Effect of debranning process on deoxynivalenol content in whole‐wheat flours. Issue 4 (29th May 2019) - Tibola, Casiane Salete; Guarienti, Eliana Maria; Dias, Alvaro Renato Guerra; Nicolau, Marcio; Devos, Rafaela Julyana Barboza; Teixeira, Daniela Dalbosco
Abstract: Background and objectives: Post‐harvest mitigation strategies are essential to reduce mycotoxin contamination in wheat‐based foods. The study aimed to evaluate the effect of the debranning process on the deoxynivalenol content in whole‐wheat flour naturally contaminated by Fusarium spp. Thirty commercial wheat samples were used and were obtained in Southern Brazil Region in 2015 crop season. Findings: The highest DON contamination level was found in the no‐debranned samples and the outermost fraction (extraction rate >95%), which corresponds to the debranning time of 15 s. When all debranning times were included in the analysis, only the samples from Paraná State had the DON content significantly reduced after the debranning. Conclusions: The debranning process reduced the DON content in whole‐wheat flour with lower to moderate levels of contamination, corresponding to DON content of 1.032 and 1.174 µg/kg, obtained in Paraná and Rio Grande do Sul States, respectively. Significance and novelty: These results are important for wheat supply chain to meet the legislation requirements and to produce safer foods.